A General Low‐Temperature Strategy to Prepare High‐Quality Metal Sulfides Charge‐Transporting Layers for All‐Inorganic CsPbI2Br Perovskite Solar Cells. Issue 7 (25th March 2022) - Chen, Weitao; Sun, Zhenxing; Guan, Xinyu; Tian, Xueying; Wang, Binkai; Zhou, Jing; Chen, Rui; Ren, Fumeng; Wang, Jianan; Liu, Sanwan; Zhang, Shasha; Liu, Zonghao; et al.
Abstract : Inorganic perovskite solar cells (I‐PSCs) have attracted great attention due to the high thermal stability of inorganic perovskites versus the organic–inorganic perovskites. To ensure the thermal stability of I‐PSCs, using effective and stable inorganic charge‐transporting layers (CTLs) to replace organic ones is quite desirable. The use of low‐temperature‐prepared inorganic CTLs can also lower the total cost of I‐PSCs. Herein, a general strategy to prepare high‐quality inorganic nanoparticles‐based electron transport layers (ETLs) below 70 °C by ligand exchange on top of inorganic perovskites is developed. The ETLs possess a suitable energy‐level structure, favorable conductivity, and chemical stability. Furthermore, all‐inorganic CTLs‐based CsPbI2 Br I‐PSCs with p–i–n architecture are fabricated without using any thermally unstable organic components. Consequently, the as‐fabricated I‐PSCs based on CdS ETLs yielded the highest power conversion efficiency (PCE) of up to 15.04%, among the most efficient CsPbI2 Br inverted PSCs. Inspiringly, the unencapsulated all‐layer‐inorganic PSCs present outstanding stabilities, which maintained 94.8% and 95.2% of their initial PCEs after aging at 85 °C in the dark and operating under continuous light illumination at 45 °C for 480 h in N2 atmosphere, respectively. Abstract : A general strategy to prepare high‐quality electron transport layers (ETLs) below 70 °C by ligand exchange on top of the inorganic CsPbI2 Br perovskite absorber layer is proposed. The ETLs possess smooth, dense, and pinhole‐free morphologies, a suitable energy‐level structure, favorable conductivity, and chemical stability, which give the whole photovoltaic devices high efficiencies and outstanding stabilities.